Pengaruh Good Corporate Governance Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Sektor Property And Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Michellia Aryanti; Ida Adhani; Rida Justin (Jurnal Ilmiah Raflesia Akuntansi, 2025)
— Research objectives: to determine the effect of corporate governance carried out by the Board of Directors, Board of Commissioners, Audit Committee, Managerial Performance and also Company Size on Financial Performance in Property and Real Estate sector companies listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling. The analysis methods used are Classical Assumption Test, Descriptive Statistics, Multiple Linear Regression, Determination Coefficient (R2), t-test and F-test. The results of the study indicate that the Board of Directors partially does not have a significant effect on financial performance, the Board of Commissioners partially does not have a significant effect on financial performance, the Audit Committee (KA) partially has a negative and significant effect on financial performance, Managerial Performance (KM) partially does not have a significant effect on financial performance, Company Size partially does not have a significant effect on financial performance. independent variables on Financial Performance are only 66.8%, meaning they are not too significant, while the remaining 33.2% are influenced by other variables outside the research variables.